Laparoscopic Resection of Advanced Colorectal Cancer in a Patient with Lumboperitoneal Shunt - Toru Imagami; Satoru Takayama; Yohei Maeda; Ryohei Matsui; Masaki Sakamoto; Hisanori Kani (Case Reports in Surgery)
A 78-year-old woman with lumboperitoneal (LP) shunt was diagnosed with advanced cancer of the ascending colon. Laparoscopic right hemicolectomy was performed without manipulating the catheter. The patient’s postoperative course was uneventful, with no shunt-related complications or neurological deficit. The number of patients with cerebrospinal fluid (CSF) shunt who require abdominal surgery has been increasing. There are only few studies on laparoscopic surgery for patients with LP shunt, and the safety of pneumoperitoneum in the CSF shunt remains controversial. Consistent with other studies, we considered that pneumoperitoneum with a pressure of 10 mmHg has few negative effects. Our recommendations are as follows: (1) during colorectal resection, laparoscopic surgery can be performed without routine manipulation of the shunt catheter; (2) altering the location of the port is necessary to prevent both damage to the shunt tube during surgery and wound infection postoperatively; and (3) laparoscopic surgery is superior to laparotomy because it is associated with reduced surgical site infections and postoperative adhesions. However, laparoscopy should be performed at least 3 months after the construction of CSF shunt.